2016
DOI: 10.1264/jsme2.me15170
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Fertilization Changes the Community Structure of Rice Root-, and Soil- Associated Bacteria

Abstract: Under paddy field conditions, biological sulfur oxidation occurs in the oxidized surface soil layer and rhizosphere, in which oxygen leaks from the aerenchyma system of rice plants. In the present study, we examined community shifts in sulfur-oxidizing bacteria associated with the oxidized surface soil layer and rice roots under different sulfur fertilization conditions based on the 16S ribosomal RNA (rRNA) gene in order to explore the existence of oligotrophic sulfur-oxidizing bacteria in the paddy rice ecosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
3
13
1
Order By: Relevance
“…This discrepancy could be due to primer bias; the primers used for soxB gene amplification amplify the soxB genes of Epsilonproteobacteria and Chloroflexi very poorly ( Meyer and Kuever, 2007 ). In addition, Bradyrhizobiaceae within Alphaproteobacteria and Burkholderiaceae within Betaproteobacteria were the dominant families in our study area; however, previous research revealed that these families might adapt to oligotrophic sulfur environments, such as soil ( Jung et al, 2005 ; Masuda et al, 2010 ) and rhizosphere soils ( Anandham et al, 2008 ; Masuda et al, 2016 ). Therefore, further study is required to determine whether the families described here are the result of contamination or actually exist.…”
Section: Discussioncontrasting
confidence: 55%
“…This discrepancy could be due to primer bias; the primers used for soxB gene amplification amplify the soxB genes of Epsilonproteobacteria and Chloroflexi very poorly ( Meyer and Kuever, 2007 ). In addition, Bradyrhizobiaceae within Alphaproteobacteria and Burkholderiaceae within Betaproteobacteria were the dominant families in our study area; however, previous research revealed that these families might adapt to oligotrophic sulfur environments, such as soil ( Jung et al, 2005 ; Masuda et al, 2010 ) and rhizosphere soils ( Anandham et al, 2008 ; Masuda et al, 2016 ). Therefore, further study is required to determine whether the families described here are the result of contamination or actually exist.…”
Section: Discussioncontrasting
confidence: 55%
“…Microbiome studies were popularized by their focus on human health, particularly the intestinal microbiota (9). They have since been applied not only to soils, but also to plant shoot and root microbiomes (31) and have provided important insights into microbial community functions in the biogeochemical cycles of carbon (10), nitrogen (25), and sulfur (15). A metatranscriptomic analysis may reveal functional microbial populations and genetic components in soil microbiomes.…”
mentioning
confidence: 99%
“…Amplicon sequence analyses of the 16S rRNA gene indicated that rice root microbiomes responded to Azospirillum sp. B501 inoculations ( 2 ) and sulfur amendments ( 23 ). The abundance of uncharacterized phylum ™7 members in rice roots was increased by sulfur amendments ( 23 ).…”
mentioning
confidence: 99%
“…B501 inoculations ( 2 ) and sulfur amendments ( 23 ). The abundance of uncharacterized phylum ™7 members in rice roots was increased by sulfur amendments ( 23 ). In addition, an inoculation experiment of non-photosynthetic Bradyrhizobium sp.…”
mentioning
confidence: 99%